Association of cigarette smoking with cardiometabolic risk factors: A cross-sectional study - Samar Sultan; Fouzy Lesloom (Tobacco Induced Diseases)
Introduction Despite strong and consistent epidemiological evidence linking cigarette smoking to several cardiovascular diseases (CVDs), the association between smoking intensity and CVD risk factors remains unclear. This study aimed to explore the possible effects of cigarette smoking on cardiometabolic risk in healthy individuals.